Central African Economic and Monetary Community : Recent Developments and Regional Policy Issues. (IMF Staff Country Reports; Country Report ;, 2003)
Macroeconomic developments in the Central African Economic and Monetary Community (CEMAC) region have been satisfactory, but risks to macroeconomic stability persist. The process of convergence remains slow and needs strengthening, notably through the adoption of a fiscal rule and the elimination of bank financing of fiscal deficits. Continued efforts by the banking regulator are needed to strengthen the banking sector. There is a need to accelerate structural reforms, strengthen basic infrastructure, and adopt common sectoral policies aimed at diversifying the regional economy.